Development Model Of Special Interest Tourism Packages Through The Exploration Of Local Wisdom In Desa Wisata Wates Jaya - Lila Muliani; Inti Krisnawati (Universitas Pendidikan Indonesia, 2022)
The aim of this study is to analyze the potential of the local wisdom in Desa Wisata Wates Jaya which can be developed into attractions in cultural and gastronomic tourism packages. Furthermore, the design of the right development model is also carried out so that the development of this tourist village can be more optimal. This research is a descriptive qualitative research with primary data obtained through observation, FDG and in-depth interviews with four informants as tourism village managers, village elders, and village culinary activists. The results showed that Desa Wisata Wates Jaya has many potential cultural and gastronomic tourism attractions which can be developed into a choice of tour packages as an alternative tourist attraction in this village. As part of special interest tourism, cultural and gastronomic tourism prepared for certain typology of tourist that is different from mass tourism tourist. Therefore, the tourism activities offered are more focused on providing experiences by engaging directly in local people's daily activities that are integrated with nature. For the development model, a modification of the Pentahelix model is designed in which the 5 elements are grouped into 3 clusters, namely the community/society and the government as the main actors, academics and business as supporters, and the media as supporters.